Tailoring The C-BARQ To Shelter Dogs: Identification Of Five Reliable Factors - Rachel J. Gilchrist; Molly J. Gardner; Patrick D. Manapat; Lisa M. Gunter; Erica N. Feuerbacher; Michael C. Edwards; Clive D. L. Wynne (Animal Behavior and Cognition)
Despite the multitude of studies on dog behavior using the Canine Behavioral Assessment and Research Questionnaire (C-BARQ), little is known about its utility in a shelter population. This study aimed to identify and validate a subset of items adapted from the C-BARQ to assess behavior in sheltered dog populations. All questionnaires were administered while the dogs were still in the shelter and were completed by shelter staff, volunteers, or members of the research team who had the most frequent interactions with the study dogs. Analysis included 445 questionnaire responses, one per dog, from 11 shelters. Exploratory (n = 222) and confirmatory (n = 223) factor analyses revealed a five-factor structure (Fear, Arousal, Human Excitability, Dog Aggression, and Human Aggression) comprising 24 items henceforth referred to as the Shelter C-BARQ. These factors exhibited above-threshold internal consistency reliability (M = .78) and meaningful inter-factor correlations, affirming their suitability for assessing the behavior of sheltered dogs. Furthermore, item response theory analysis underscored the reliability and validity of these items in measuring the underlying constructs. These findings can be particularly valuable for shelters facing resource constraints, offering both efficiency and validated data collection methods to collect behavioral information.